The Cambridge companion to Gandhi - Brown, Judith M. (Judith Margaret), 1944-; Parel, Anthony (Cambridge University Press, 2011)
"Even today, six decades after his assassination in January 1948, Mahatma Gandhi is still revered as the father of the Indian nation. His intellectual and moral legacy, encapsulated in works such as Hind Swaraj, as well as the example of his life and politics serve as an inspiration to human rights and peace movements, political activists, and students in classroom discussions throughout the world. This book, comprised of essays by renowned experts in the fields of Indian history and philosophy, traces Gandhi's extraordinary story." -- Από τον εκδότη.